Hannah Arendt and International Relations : Readings Across the Lines - Lang, Anthony F.; Williams, John. (Basingstoke : Palgrave Macmillan, 2008)
Featuring scholars in International Relations theory, this book fills a gap in literature on international thought. It's approach to politics focuses on action and conduct, rather than institutions, constitutions, and states. It also features essays that challenge conventional IR theories.
Why Hannah Arendt?; A. Lang Jr. and J. Williams; Hannah Arendt:National Sovereignty, Rights, and Responsibility; D Klusmeyer; Governance and Political Action: Hannah Arendt on Global Political Protest; A. Lang Jr.; Hannah Arendt and the International Space In-between; J. Williams; Between International Politics and International Ethics; A. Lang Jr. and J. Williams. / A Biographica and Political Introduction; P. Owens; Hannah Arendt, Publics and Violence; P. Owens; Forgiveness and the Possibility of Politics in Post-Conflict Situations A. Schaap; Hannah Arendt and the "Right" to Have Rights; B. Cotter; Hannah Arendt's Critical Realism.
Includes bibliographical references and index.
Keywords: Arendt, Hannah, -- 1906-1975.; International relations